Process method of Si3N4 ceramic brazing sealed cavity for high-temperature application - Li, Chen; Fang, Zhihong; Sun, Boshan; Xiong, Jijun; Xu, Aodi; Guo, Ximing; Hong, Yingping (Frontiers in Chemistry, 2022)
The process method of a Si3N4 ceramic sealed cavity is realized by vacuum brazing and chemical reaction at 1,100°C and 0.5 MPa pressure. Through the combination of Si3N4 ceramic polishing and thinning, inductively coupled plasma etching, and high-temperature metal filler (Ti-Zr-Cu-Ni) brazing process, a vacuum-sealed cavity suitable for high-temperature environments was prepared. The cross section of the bonding interface was characterized by scanning electron microscope (SEM) and energy dispersive spectrometer (EDS), which indicated that the two Si3N4 ceramic were well bonded, the cavity structure remained intact, and the bonding interface strength exceeded 5.13 MPa. Furthermore, it retained its strong bonding strength after in high-temperature environments of 1,000, 1,050, and 1,100°C for 1 h. This indicates that a brazed vacuum-sealed cavity can be used in high-temperature environments. Through the proposed method, pressure sensor that can withstand high temperatures can be developed.